Association Between Endothelial Alterations, Cardiac Function, and Outcomes From Health to Heart Failure: Insight From the STANISLAS, MEDIA‐DHF, and BIOSTAT‐CHF Cohorts - Jeremy Lagrange; Mohammad Jahangiri; Guillaume Baudry; Nathalie Mercier; Luca Monzo; Zohra Lamiral; Kévin Duarte; Jozine M ter Maaten; Faiez Zannad; Adriaan A. Voors; Nicolas Girerd (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Heart failure with preserved ejection fraction (HFpEF) is a multifaceted syndrome, likely stemming from comorbidity‐induced inflammation resulting in endothelial dysfunction. Endothelial glycocalyx degradation's role in the development and prognosis of HFpEF remains largely unexplored. Our study aimed at exploring the association between glycocalyx degradation and diastolic dysfunction and determining whether glycocalyx degradation can predict clinical outcomes in patients with HFpEF. Methods Perlecan and thrombomodulin concentrations were assessed in individuals deemed healthy (STANISLAS [Suivi Temporaire Annuel Non‐Invasif de la Santé des Lorrains Assurés Sociaux (Annual Noninvasive Temporary Monitoring of the Health of Insured Lorrainers)] cohort, n=1705) and patients with HFpEF (MEDIA‐DHF [Metabolic Road to Diastolic Heart Failure], n=460 and BIOSTAT‐CHF [Biology Study to Tailored Treatment in Chronic Heart Failure], n=556) to evaluate endothelial glycocalyx degradation. Results In patients with HFpEF, perlecan but not thrombomodulin was increased compared with controls (P<0.0001 versus P=0.73). In adjusted analysis, perlecan was associated with peak early mitral inflow velocity/peak early diastolic mitral annular velocity ratio and thrombomodulin with peak early diastolic mitral annular velocity in control individuals, whereas perlecan and thrombomodulin were associated with peak early mitral inflow velocity/peak early diastolic mitral annular velocity and left atrial volume index in patients with HFpEF (all P<0.03). Perlecan was significantly associated with cardiovascular hospitalization and death in the MEDIA‐DHF (adjusted hazard ratio [HR] for highest tertile versus first tertile, 2.44 [95% CI, 1.11–5.34]; P=0.026) and BIOSTAT‐CHF cohorts (adjusted HR, 2.12 [95% CI, 1.49–3.03]; P<0.0001). Thrombomodulin was associated with a worse outcome in BIOSTAT‐CHF (P=0.004) but not in MEDIA‐DHF. Conclusions Higher circulating levels of the endothelial glycocalyx degradation biomarkers like perlecan and, to a lesser extent, thrombomodulin are associated with features of diastolic dysfunction in population and HFpEF settings and predict poor outcome in patients with HFpEF. These results suggest that glycocalyx degradation may be an early step in the pathological processes leading to HFpEF and gain further prognostic value in later stages (ie, overt HFpEF). Registration URL: https://clinicaltrials.gov/; Unique identifiers: NCT01391442, https://clinicaltrials.gov/study/NCT01391442?cond=stanislas&rank=1; NCT02446327; URL: https://cordis.europa.eu; BIOSTAT‐CHF ID: 242209.